Numerical Simulation of Seakeeping Performance of a Barge Using Computational Fluid Dynamics (CFD)-Modified Potential (CMP) Model - Seol Nam; Jong-Chun Park; Jun-Bum Park; Hyeon Kyu Yoon (Journal of Marine Science and Engineering, 2024)
This paper explains the evaluation process of seakeeping performance for small vessels using a CFD-modified potential (CMP) model, a hybrid simulation model that modifies the damping ratio with computational fluid dynamics (CFD) after analyzing ship motion based on the linear potential theory. From the result of the motion analysis using the CMP model, the seakeeping performance of a small vessel (a barge here) was evaluated on the basis of the single significant amplitude (SSA) under the sea states 2~4. The results of the motion RAOs and seakeeping performance evaluation were verified through comparison with the results obtained by performing model tests and potential flow programs only. In all sea states, the relative errors (compared to the experiment) of roll motion using the CMP model were relatively small compared to the results using the potential flow program and tended to decrease more as the sea state increased. On the other hand, the results of pitch motion using the CMP model were underestimated in all sea states compared to the experiment. However, it is seen that they are relatively closer to the experiment compared to the results using a potential flow program only.